Prevalência dos hábitos orais parafuncionais na população com disfunção temporomandibular: uma revisão sistemática - Silva, Juliana Leite da (2022)
Temporomandibular Dysfunction as the term that refers to the abnormalities that affect the temporomandibular joints and/or the muscles of mastication. Parafunctional oral habits are considered as any movement other than those performed functionally or performed excessively by the temporomandibular joints, which can be day or night, and are identified as one of the possible risk factors for the development of such a disorder. Given these observations, the objective of this review is to identify the prevalence of parafunctional oral habits in the population with temporomandibular disorders. This systematic review was carried out in accordance with the Preferred Items for Reporting on Systematic Reviews and Meta-Analyses (PRISMA) guidelines, using observational (cross-sectional) studies produced up to November 2022 as sources, written in English, Portuguese or Spanish and collected in MEDLINE, BVS, SciELO, LILACS, EMBASE databases. The parafunctional habit with the highest prevalence in the population with temporomandibular disorders is bruxism, it was also noticed that there is a wide variety of parafunctional habits mentioned in the literature and there is no standard among the authors regarding which habits are included in their studies, in all 30 divergent parafunctional habits were identified in this review. The presence of parafunctional habits aggravate the signs and symptoms of individuals with temporomandibular disorders, due to hyperactivity of the masticatory muscles.